PENGENDALIAN SUMBER DAYA MANUSIA PADA KARYAWAN UNIVERSITAS WIRARAJA BAGIAN STRUKTURAL DALAM PENCAPAIAN PRESTASI KERJA - Dedy Arfiyanto; Isnani Yuli Andini (Fakultas Ekonomi dan Bisnis, 2016)
Human being as human resource represent labour if only evaluated from its just physical. With all ability of his physical try to fulfill requirement of his life by taking benefit around its environment. Human resource in an organization represent top-drawer determinant to effectiveness of labour capacity and organization. The succes in work area in organization determined by interest storey, professionalism and his work which is Wiraraja. University of Wiraraja as organization is non profit need ability to accept and adapt to various friction and change of environment/climate, passing management of SDM capable to esteem human being standing and prestige. In approach of SDM mean all and every organization have to can create satisfaction and security in working (Quality of Work Life) brief of QWL, so that his environmental SDM become competitif.Research Type is used in this research is qualitative research. By using qualitative method, researcher involve direct and continue to have interaction with source of data so that operation of Human Resource data at Employees University of Wiraraja Structural Shares can know clearly.Result of research can be concluded that recruitment of officer candidate in University of Wiraraja at order officer of Year 2015 with conditions of public and conditions of administration which consist in officer order section 12 article 1 and 2. Training and development of officer have been budgeted by Foam Proffering of Budget (direct guarded DIPA) by Bureau Financial Administration ( BAKU) but training amount still minim and officer in evaluation by each head of satker, but follow-up result of evaluation still discipline, but position/occupation promotion even increase of officer salary still conducted at a time per annum non seeing from performance, dedication, its officer achievement and also loyalities. Keyword : Operation of Human Resource, Labour Capacity